Coimmobilization of different lipases: Simple layer by layer enzyme spatial ordering - Peña, Sara Arana; Rios, Nathalia Saraiva; Sanchez, Carmen Mendez; Lokha, Yuliya; Carballares, Diego; Gonçalves, Luciana Rocha Barros; Lafuente, Roberto Fernandez (International Journal of Biological Macromolecules, 2021)
This paper shows the step by step coimmobilization of up to five different enzymes following two different orders in the coimmobilization to alter the effect of substrate diffusion limitations. The enzymes were the lipases A and B from Candida antarctica, the lipases from Rhizomocur miehei and, Themomyces lanuginosus and the phospholipase Lecitase Ultra. The utilized strategy was a layer by layer immobilization, coating the immobilized enzymes with polyethylenimine followed by the crosslinking of the enzyme and PEI with glutaraldehyde to prevent enzyme release, and them adding a new lipase layer. The use of previously inactivated biocatalysts (using diethyl p-nitrophenylphosphate) permitted to visualize the immobilization of each enzyme layer, which was later confirmed by SDS-PAGE. This also confirmed the successful and complete covalent crosslinking of the glutaraldehyde treated enzyme layers. Activity of the combibiocatalysts was followed using diverse substrates. The protocol was successful and permitted to immobilize in an ordered way the 5 different enzymes in a down-up distribution 2030-12